The design of smart notification on android gadget for academic announcement - Agustina Heryati; Evi Yulianti; Faradillah Faradillah; Dewi Sartika; Dhamayanti Dhamayanti; Imelda Saluza; Ahmad Sanmorino (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this article, we try to design the architecture of a smart notification system using an Android gadget for academic notification in college. Academic notification in colleges now utilizes bulletin boards and online media such as websites or social media. The problem faced is the high cost and resources required to deliver the academic notification. Another problem is whether the information delivered can be right to the students who need it. We proposed the architecture of a smart notification system that can reduce the cost, and the information delivered can be right on target to the students in need.